Grating Spectrometer using Compact Disc - เจ๊ะมะ นัสรีนา; สามะ อามานี; เละนุ๊ นูรซีลา (YRU Journal of Science and Technology, 2018)
This research aimed to create the Grating Spectrometer by using the compact disc. The Grating Spectrometer is an instruction media, used in the experiment especially in the dark lab. Experimental equipments are the Grating, the Hydrogen spectrum tube and the compact disc using for replacing the standard grating. According to the comparison with the standard wavelength, the measured wavelength from the compact disc is, the percentage error of less than 5%. The percentage error of purple, green and red colors for grating are 1.23%, 1.06% and 0.45%, respectively and those for compact disc are 2.09%, 0.95% and 0.60%, respectively. It can be seen that the spectrum obtained from experiments using compact disc grating spectrometer can nearly provide to standard.